Creating new states in India: Chattisgarh, Jharkhand, Uttaranchal - Rothermund, Dietmar (Asien, 2001)
Indian federalism is a very flexible institution. Due to its centralist bias it can be easily used by the Government of India for its own ends. This has now been demonstrated by the present coalition government led by the Bharatiya Janata Party (BJP) which has created three new states by means of "reorganisation" acts passed by the central parliament. The earlier round of such reorganisations in Nehru's times were based on the report of the States Reorganisation Commission of 1955 which followed the principle of linguistic boundaries. Nehru had only reluctantly agreed to this reorganisation, and as far as the separation of Gujarat and Maharashtra was concerned he postponed until 1960. When Goa was liberated from Portuguese rule in 1961 and the majority of its electorate voted for a party which advocated the merger of Goa with Maharashtra, he prevented the merger and saw to it that Goa remained a Union Territory. In subsequent years some small states were created in order to accommodate ethnic interests, particulary in the tribal belt of Northeastern India. The latest round of this kind was in 1987 when Mizoram became a state at the same time when Goa was promoted from the status of a Union Territory to a state.
Elektronische Reproduktion der Druckausgabe
Keywords: Indien